PENERAPAN MODEL PEMBELAJARAN STAD (STUDENTS TEAMS ACHIEVEMENT DIVISIONS) SEBAGAI UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA KELAS XI DI SMK MUHAMMADIYAH 3 YOGYAKARTA TAHUN AJARAN 2015/2016 - Ilyasa Ilyasa; Setuju Setuju (Jurnal Taman Vokasi, 2016)
Application of Learning Model Students teams achievement divisions (STAD) As Efforts to Improve Achievement Motivation and Learning Theory Tool Engineering Students in grade XI In SMK Muhammadiyah 3 Yogyakarta Academic Year 2015/2016. Thesis Mechanical Engineering Study Program of the Faculty of Education University of Sarjanawiyata Tamansiswa Yogyakarta, 2016.            The purpose of research to enhance the activity and student achievement by improving the learning process engineering theory subjects lathe through learning model Students Teams Achievement Divisions (STAD). Teachers presents the objectives, learning issues, students carry out group discussions, exercises and debriefing, strengthening and conclusions on the subjects of engineering theory lathe in SMK Muhammadiyah 3 Yogyakarta academic year 2015/2016, the study subjects were students of class XI TP 1 as 31 students. This research is a classroom action research (Classroom Action Research) were carried out with 3 cycles. Each cycle begins meetings held twice a planning stage action, action execution, observation, and reflection. Methods of data collection is done by observation and tests. Data analysis was carried out by comparison between the results in the first cycle, second cycle and third cycle with descriptive techniques. This means that from the data obtained in this study are presented what was then analyse descriptively to obtain an overview of the facts and the corresponding descriptions phenomenon. As well as to measure student achievement using the system the difference in value between pretest and posttest on evaluation of each cycle. The results represent that the activity and student achievement class XI TP 1 SMK Muhammadiyah 3 Yogyakarta in theory lessons lathe techniques of the first cycle, second cycle and third cycle increased. Students' learning activeness of the first cycle of 34,11% increase the second cycle to be 51,16% and the third cycle increased to 70,55%. Likewise, learning achievement increased from an average value of 48,88 pretest to posttest increased first cycle of 69.68 is further increased to the second cycle into 74,20 posttest and posttest third cycle increased again to 77,75.